Quantifying Ocean-Atmosphere-Ecosystem Coupling: Precipitation-Chlorophyll Lag Relationship in West Java Using Decade-Long Satellite Observations - Muhammad Fatan Rzaqa; Satria Sandi Pratama; Carolina Angel; Nailil Izzah; Haura Azalia Putri Fardian; Jogi Panggabean (Jurnal Ilmiah Multidisiplin Indonesia (JIM-ID), 2026)
Understanding predictive relationships between oceanic conditions and extreme rainfall is crucial for improving weather forecasting capabilities in tropical maritime regions. This study investigates quantitative relationships between precipitation, chlorophyll-a concentrations, and extreme rainfall patterns in West Java using 10 years of satellite observations (2014-2024). We analyzed IMERG precipitation data and MODIS chlorophyll-a products using cross-correlation analysis, continuous wavelet transform, cross-wavelet coherence, and spatial extreme indices calculations. Results reveal statistically significant coupling between precipitation and chlorophyll-a (r = -0.173, p < 0.001) with precipitation leading chlorophyll decrease by 19 days, reflecting marine ecosystem responses to terrestrial runoff. Cross-wavelet coherence analysis demonstrates 78% annual coherence and 68% semi-annual coherence between these variables, with 72.5% of total variance explained by significant periodic interactions. Wavelet analysis identifies dominant annual and semi-annual cycles in both precipitation and chlorophyll-a with 95% statistical significance. Spatial analysis using k-means clustering reveals four distinct precipitation regimes: northern coastal zones with prolonged dry periods (>45 days), central highlands with intense convective activity (>3000 mm annually), southern mountains with extreme precipitation (>3200 mm), and transitional zones with mixed characteristics. Spatial autocorrelation analysis confirms significant clustering (Moran's I = 0.65-0.89) of precipitation extremes across the region. The identified 19-day lead-lag relationship provides a scientific foundation for marine ecosystem monitoring and represents a significant advancement in understanding ocean-atmosphere-ecosystem coupling processes in tropical Indonesia. These findings have important implications for developing improved seasonal forecasting capabilities and ecosystem-based climate adaptation strategies. Keywords: Climate variability; Extreme precipitation; Lead-lag correlation; Tropical meteorology; Wavelet analysis; Cross-wavelet coherence; Marine ecosystems